Application of Magnetic Methods for Estimating Subsurface Rocks - Maubana, Wenti Marlensi (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
The magnetic method has been applied to the estimation of subsurface rocks in North Pura, Alor Nusa Tenggara Timur (NTT). The magnetic survey was performed using Proton Precession Magnetometer (PPM) type G-19T and measured on 54 magnetic stations. The magnetic data were processed by diurnal correction, IGRF correction, upward continuation, and 2D data modeling. The results showed that total magnetic intensity ranged from 50 nT to 770 nT. The regional anomaly contour map showed at the research area was dominated by the moderate anomaly. Estimation of subsurface profiles has been 2D forward modeling used regional anomaly of a contour map. The results showed that subsurface rocks in the research area. It's suspected was three types of rock in the research area as the volcanic sandstone, volcanic breccias, and basalt with a contrast susceptibility value of 0.0001 cgs unit, 0.0015 cgs unit, 0.0278 cgs unit, 0.0091 cgs unit, 0.0099 cgs unit, and 0.0134 cgs unit. The research study is expected to provide information for the local government especially in north Pura for in the existence of groundwater, depth and distribution of subsurface rocks.